KEMULIAAN WANITA DALAM CERITA SABHA PARWA - Ningsih, Ni Made Tisna; Subagia, I Nyoman; Suwantana, I Gede (Pangkaja: Jurnal Agama Hindu, 2024)
The glory of women in the story Sabha Parwa from the Mahabharata reflects the values ​​and beliefs underlying Hindu theology about the role of women in society and spirituality. This research aims to explore the understanding of the glory of women in this Hindu epic story from a theological perspective. The background to the issue highlights the importance of understanding the role of women in classical Hindu literary works to strengthen the values ​​of gender equality and respect cultural heritage. The research method used is text analysis, focusing on the main female characters in the Sabha Parwa story such as Kunti, Draupadi, and Gandhari. The analysis was carried out by considering the cultural, social and theological context at the time the Mahabharata was written, as well as the interpretation of the text by Hindu scholars. The research results show that the nobility of women in the Sabha Parwa story is reflected in their role as family protectors, wise advisors, and moral pillars. These women display courage, loyalty, and wisdom in facing life's trials, which is considered a manifestation of aspects of the goddess in Hindu tradition. The theological implications of this research highlight the importance of respecting the role of women in society and integrating Hindu spiritual values ​​in everyday life. Women in the story of Sabha Parwa are glorified for their role as guardians of the family, bearers of wisdom, and moral pillars. They demonstrate courage, loyalty, and wisdom in facing life's trials, which is considered a manifestation of aspects of the goddess in Hindu tradition. The implication of the glorification of these women in Hindu stories is the recognition of their spiritual power, wisdom, and contribution in maintaining balance in the universe. This research provides a deeper understanding of the glory of women in the story of Sabha Parwa from the perspective of Hindu theology, and emphasizes the importance of appreciating and understanding the role of women in Hindu cultural heritage and spirituality. The glorification of women in the story of Sabha Parwa reflects Hindu theological values ​​which respect the role of women as symbols of spiritual strength and wisdom, and strengthens the importance of gender equality and respect for diversity in Hindu society.